Harmful algal blooms in agricultural irrigation: risks, benefits, and management - Newton, Amanda Rose; Melaram, Rajesh (Frontiers in Water, 2023)
Harmful algal blooms (HABs) have garnered increasing attention due to their adverse effects on water quality, aquatic ecosystems, and animal and human health. Prior research suggests that HAB-contaminated water containing toxins can significantly affect the development of plant structures and inhibit essential physiological processes. However, the potential benefits and risks of using HAB-contaminated water sourced from local water bodies for agricultural irrigation is not completely understood. This perspective paper delves into the origins and impacts of HABs, the environmental and agricultural repercussions of their use in irrigation, and management strategies to mitigate associated risks of HAB-contaminated water in sustainable agriculture. Future studies are needed to validate the practical benefits of HABs in agricultural irrigation for the enhancement of soil health and overall crop growth and productivity.